Pedagogical Model Innovation in Early Childhood Education: A Systematic Literature Review on Child Development, and the Role of the Family - Rahman Febrian; Moh Yaqob (Journal of Early Childhood Education Perspectives, 2025)
This systematic literature review examined the latest innovations in early childhood pedagogical models by synthesizing 45 peer-reviewed studies published in the last five years. These findings reveal that early childhood education is undergoing a significant transformation characterized by a pedagogical approach that is child-centered, inclusive, and technology-supported. Play-based learning, early STEM integration, digital learning tools, project-based activities, and multimodal literacy have emerged as key innovations that improve children's cognitive, social-emotional, language, and creative development. This review highlights that effective pedagogical innovation requires not only methodological advancements but also paradigm shifts in the way young children learn and interact in their learning environment. Family involvement was identified as a central determinant of pedagogical effectiveness. Home-school collaboration, parent involvement, and structured family-based learning activities strengthen continuity between home and school, thereby improving children's developmental outcomes. The review further emphasizes the role of inclusive education models, particularly the use of differentiated teaching, Universal Design for Learning (UDL), and culturally responsive pedagogy. This approach ensures that learning spaces accommodate the diverse needs of children, including those with special educational needs, while fostering empathy, collaboration, and social identity development. Overall, the review concludes that the most effective pedagogical innovations in early childhood education are those that integrate constructivist principles, active family participation, and inclusive learning practices. These findings underscore the need for ongoing professional development for educators, institutional support systems, and sustainable implementation strategies. This study contributes to shaping a future early childhood education model that is holistic, equitable, and responsive to the evolving needs of young learners.